2021
DOI: 10.1002/aur.2543
|View full text |Cite
|
Sign up to set email alerts
|

Cataloguing and characterizing interests in typically developing toddlers and toddlers who develop ASD

Abstract: Intense interests are common in children with and without autism spectrum disorder (ASD), and little research has characterized aspects of interests that are unique to or shared among children with and without ASD. We aimed to characterize interests in a sample of infants at high‐familial‐risk (HR) and low‐familial‐risk (LR) for ASD using a novel interview. Participants included HR siblings who were diagnosed with ASD at 24 months (HR‐ASD, n = 56), HR siblings who did not receive an ASD diagnosis at 24 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Further, RI and UI also emerged as distinct factors in a factor analysis of a recently developed RRB measure (Dimensional Assessment of Repetitive Behavior [DARB;) that was specifically designed to comprehensively capture a wide range of RRB, including CI. Finally, in a recent longitudinal study of infants, Burrows et al (2021) reported that the presence of UI, more so than the intensity of CI, was a stronger predictor of later autism diagnoses, demonstrating the utility of distinguishing between these constructs. However, it is currently unclear if different manifestations of CI, including RI and UI; vary depending on individual characteristics such as age, sex, cognitive functioning, and core autism characteristics.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, RI and UI also emerged as distinct factors in a factor analysis of a recently developed RRB measure (Dimensional Assessment of Repetitive Behavior [DARB;) that was specifically designed to comprehensively capture a wide range of RRB, including CI. Finally, in a recent longitudinal study of infants, Burrows et al (2021) reported that the presence of UI, more so than the intensity of CI, was a stronger predictor of later autism diagnoses, demonstrating the utility of distinguishing between these constructs. However, it is currently unclear if different manifestations of CI, including RI and UI; vary depending on individual characteristics such as age, sex, cognitive functioning, and core autism characteristics.…”
Section: Introductionmentioning
confidence: 93%
“…Regardless of assessment modality, studies have consistently found that CI are highly frequent, with upwards of 75% of autistic individuals presenting with at least one, and often multiple, CI (Klin et al, 2007;Uljarevi c, Alvares, et al, 2021). Beyond frequency, studies using comprehensive CI assessments-such as the Interests Scale (Bodfish et al, 2004), the Yale Survey of Special Interests (Klinet al, 2007), and the Special Interests Motivation Scale (Grove et al, 2016)-have demonstrated the complexity and diversity of interests and behaviors encompassed in this domain (Anthony et al, 2013;Burrows et al, 2021;Klin et al, 2007;Turner-Brown et al, 2011). For example, whereas some CI are characterized by high intensity and inflexibility, but are otherwise centered around topics that are not unusual in themselves (e.g., video games or dinosaurs), other CI pertain to topics or objects that are generally not salient in nonautistic populations (e.g., telephone poles or shower heads).…”
Section: Introductionmentioning
confidence: 99%
“…There are some additional important limitations of this work that are important to acknowledge. First, the developmental timing of focused interests is variable across studies, with some indicating that focused interests are established by the preschool years (Alexander et al, 2008; Burrows et al, 2021; DeLoache et al, 2007) and others suggesting an onset closer to age 5 (Nowell et al, 2021). If interests generally emerge closer to age 5, then a slightly older sample than the one we report here might be valuable.…”
Section: Discussionmentioning
confidence: 99%
“…“Restricted and repetitive interests” are included as one of the diagnostic features of Autism Spectrum Disorder (APA, 2013), and strong interests are experienced by the vast majority of autistic individuals (Grove et al, 2018; Klin et al, 2007; Nowell et al, 2021; Spiker et al, 2011). Although the intensity of interests may be stronger in autistic individuals than in people who do not have autism (Anthony et al, 2013; Burrows et al, 2021; Larose et al, 2021), the number and topic of interests may be similar (Anthony et al, 2013), including television, animals, construction, and art (Nowell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Few endophenotypes have been identi ed in ASD, though several trait dimensions have shown promise for assessing familial risk. For example, "broader autism phenotypic" (BAP) traits, including social aloofness, communication di culties, and rigid personality traits, are more prevalent in unaffected family members of autistic individuals relative to the non-autistic population [9][10][11][12]. Cognitive processing de cits, including reduced behavioral exibility and inhibitory control, also are associated with core autism traits and disrupted in unaffected parents compared to age-matched controls [13].…”
Section: Introductionmentioning
confidence: 99%